PENGAMBILAN KEPUTUSAN TENAGA KERJA INDONESIA (TKI) PEREMPUAN UNTUK BEKERJA DI LUAR NEGERI: KASUS KABUPATEN CILACAP - Aswatini Raharto (Jurnal Kependudukan Indonesia, 2017)
In the past, women migrants are considered as passive migrants following their parents or husbands. However, the increasing number of Indonesian women migrating to work abroad, even outnumbering men, suggests the importance of understanding the reasons underlined their movements. This article examines the decision-making process of working abroad among the returned Indonesian women migrants. A quantitative approach was used to analyze secondary data from several government institutions. Also, the qualitative approach was utilized to understand the migration decision-making process. The study was conducted in Cilacap District, one of the major labor migrant sending districts in Indonesia. The result showed that women have no other choice than working abroad, mainly due to the economic reason. Moreover, the initiative to work abroad commonly comes from the women themselves, while other family members, especially father and husband, only give their consent. It can be said that women are more autonomous and self-assured when deciding to work abroad.Â